IMMUNOEXPRESSION OF CD-10 IN BASAL CELL CARCINOMA AND SQUAMOUS CELL CARCINOMA OF HEAD AND NECK - Ilyas, Maria; Rafiq, Muhammad Yasir; Farhan, Farha; Ali, Misbah; Afzal, Saeed; Niazi, Zainab (Pakistan Armed Forces Medical Journal, 2021)
Objective: To compare the expression of CD-10 in basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). Study Design: Comparative cross-sectional study. Place and Duration of Study: Armed Forces Institute of Pathology, Rawalpindi, from Jun 2016 to Jun 2017. Methodology: After taking ethics approval from the ethical review committee AFIP, previously diagnosed, thirty-eight cases of each basal cell carcinoma and squamous cell carcinoma were taken from the histopathology department of Armed Forces Institute of Pathology, Rawalpindi. CD-10 was applied according to standard protocol. The intensity of the CD-10 expression is assessed and categorized into three groups. CD-10 expression less than 10% in the tumour cell was taken as negative (-), 10 to 50% staining was taken as positive (+) and greater than 50% staining in tumour cells was taken as strong positive (++). Results: Out of the total 76 cases included in the study, 9 (24%) were strongly positive (++) whereas 20 (52.6%) were positive (+) and 9 (23.7%) were negative (-) for CD-10 expression. Out of the total 38 cases of SCC 4 (11%) cases showed positive CD-10 expression and 34 (89%) showed negative (-) results. A significant association (p-value <0.001) was seen when CD-10 expression in BCC was compared with SCC. Conclusion: CD-10 expression was higher in basal cell carcinoma when compared to squamous cell carcinoma in which CD-10 expression was very low/absent, hence CD-10 can serve as a useful adjunct marker in differentiating between basal cell carcinoma and squamous cell carcinoma in problematic cases.